Wage, income and consumption inequality in Japan, 1981-2008: From boom to lost decades - LISE, Jeremy (Institutional Knowledge at Singapore Management University, 2014)
In this paper we document the main features of the distributions of wages, earnings, consumption and wealth in Japan since the early 1980s using four main data sources: the Basic Survey on Wage Structure (BSWS), the Family Income and Expenditure Survey (FIES), the National Survey of Family Income and Expenditure (NSFIE) and the Japanese Panel Survey of Consumers (JPSC). We present an empirical analysis of inequality that specifically considers the path from individual wages and earnings, to household earnings, after-tax income, and finally consumption. We find that household earnings inequality rose substantially over this period. This rise is made up of two distinct episodes: from 1981 to 1996 all incomes rose, but they rose faster at higher percentiles; from 1996 to 2008 incomes above the 50th percentile remained flat but they fell at and below the 50th percentile. Inequality in disposable income and in consumption also rose over this period but to a lesser extent, suggesting taxes and transfers as well as insurance channels available to households helped to insulate household consumption from shocks to wages. We find the same pattern in inequality trends when we look over the life cycle of households as we do over time in the economy. Additionally we find that there are notable differences in the inequality trends for wages and hours between men and women over this period.